Analýza a řízení rizik sportovního klubu - Pospíšil, Pavel (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2024)
Diplomová práce se zabývá řízením rizik univerzitního hokejového týmu VUT Cavaliers Brno. V první, teoretické, části práce jsou popsány základní pojmy související s managementem rizik. V druhé, praktické části diplomové práce, jsou provedeny analýzy možných rizik pro interní a extérní aspekty hokejového týmu, jejichž cílem je podat ucelený a komplexní přehled. V závěru práce je posouzena jejich závažnost a jsou navržena opatření, která sníží jejich míru.

This master´s thesis deals with risk management associated with university hockey team VUT Cavaliers Brno. Firstly, in the theoretical part of the thesis, there are described the basic concepts related to risk management. Secondly, in the practical part of the thesis, there are provided analyses of possible risks for the internal and external aspects of the hockey team. Their aim is to provide a comprehensive overview. Finally, there are analysed possible risks, asses their magnitude, and propose measures that mitigate the risk.
Risk analysis and Risk Management for Sport Organization
Keywords: Riziko; analýza rizik; PESTLE; PORTER; matice rizik; Risk; risk analysis; PESTLE; PORTER; risk matrix